1986
DOI: 10.1172/jci112274
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal parathyroid hormone stimulation of 25-hydroxyvitamin D-1 alpha-hydroxylase activity in the hypophosphatemic mouse. Evidence for a generalized defect of vitamin D metabolism.

Abstract: Abnormal regulation of vitamin D metabolism is a feature of Xlinked hypophosphatemic rickets in man and of the murine homologue of the disease in the hypophosphatemic (Hyp)-mouse.We previously reported that mutant mice have abnormally low renal 25-hydroxyvitamin D-la-hydroxylase (la-hydroxylase) activity for the prevailing degree of hypophosphatemia. To further characterize this defect, we examined whether Hyp-mouse renal la-hydroxylase activity responds normally to other stimulatory and inhibitory controls of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 35 publications
4
24
1
Order By: Relevance
“…The present findings, together with the results ofour earlier reports (4,8), support the hypothesis that enzyme activity in the Hyp-mouse model of XLH is abnormally regulated by factors that influence enzyme function in the PCT. In contrast, enzyme function in the PST is normally modulated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present findings, together with the results ofour earlier reports (4,8), support the hypothesis that enzyme activity in the Hyp-mouse model of XLH is abnormally regulated by factors that influence enzyme function in the PCT. In contrast, enzyme function in the PST is normally modulated.…”
Section: Discussionsupporting
confidence: 90%
“…In subsequent studies, played a significantly lesser fourfold increment, similar to previously reported observations (8). In contrast, a maximal stimulatory dose of calcitonin (1.25 IU/h) resulted in an identical increase of 25(OH)D-la-hydroxylase activity in both the normals and the mutants, as reported above.…”
Section: Methdds Animalssupporting
confidence: 88%
See 1 more Smart Citation
“…However, these investigations did not include examination of many of the classic biochemical defects characteristic of XLH. In this regard, previous work has established that Hyp mice exhibit abnormal phosphate/PTH regulation of renal 25-hydroxyvitamin D (25[OH]D)-1 a-hydroxylase activity (10)(11)(12)(13). Thus, in the present study we tested for the presence of genetically determined biochemical heterogeneity by examining if Gy mice exhibit disparately regulated calcitriol production.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bone microradiographs from patients with XLH have shown the presence of defective mineralized bone ( Figure 5, C and D), which could reduce PTH-induced release of calcium from bone. PTH administration in Hyp mice also has little effect on 1,25(OH) 2 D levels (72,73).…”
Section: Other Potential Phosphatonin/minhibins In Xlhmentioning
confidence: 97%